Grundtvig som fortolker af Det Gamle Testamente - Høgenhaven, Jesper (Grundtvig-studier, 2011)
Grundtvig som fortolker af Det Gamle Testamente[Grundtvig 's reception of the Old Testament]By Jesper Høgenhaven This article analyses aspects of Grundtvig’s reception of the Old Testament. In his historical works from 1812, 1814, and 1833, Grundtvig makes a number of important remarks on the role and significance of the Old Testament. His position has sometimes been characterised as “fundamentalist”, but as is shown in a discussion with recent contributions (Ole Vind, Kim Ame Pedersen), this is hardly a precise description. While Grundtvig repeatedly defends the Old Testament texts as historically reliable - and as authentic prophecies related to the coming of Christ - and makes polemic remarks against historical criticism, he nevertheless demonstrates a critical position regarding the canonical status of Old Testament books, and in his later works, he explicitly renounces the doctrine of verbal inspiration and directs polemical remarks at both rationalists and orthodox adherents of verbal inspiration. The Jewish scriptures are not the foundation upon which the church is built, as the orthodox theologians would have it. This does not mean that the Old Testament loses its importance for Grundtvig. His work amply demonstrates the centrality of biblical texts and motifs. In his sermons he makes extensive use of Old Testament quotations, interpreting them according to the classic patterns as prophecies directly relevant for the church, or as typological models for Christians. What is interesting, however, is that whereas explicit quotations are found less frequently in Grundtvig’s later sermons, his sermons are permeated with biblical motifs and imagery from the Old Testament. In his hymns, he achieves the creation of a universe which is biblical in a comprehensive sense.